Enlightenment and Ontology. Ontological Aspects of Enlightenment-in-Russia - Kuznetsov, Vsevolod (Sententiae, 2015)
In this article the author continues to analyze the specifics of borrowed Enlightenments. The Enlightenment in question is the one that came from Europe to Russia during the 18th century. The author shows that when a borrowed Enlightenment enters into another civilization, it has to change itself in order to be connected to indigenous ontological mechanisms and has to rebuild these mechanisms in order to adapt them to its own needs. In Russia the borrowed Enlightenment affects local ontological mechanisms that are in the state of crisis, and contributes to their further erosion. On the other hand, the cooperation with Russian ontological mechanisms starts the process of irreversible changes of the Enlightenment-in-Russia and causes its transformation into the Russian Enlightenment.